The Role of Government Control on Consumer Behavior to be Environmentally Oriented - Muchsin Saggaff Shihab, Dipa Mulia, (Jurnal Manajemen, 2021)
Consumer orientation towards Green Products or environmentally friendly products is one of the supporting factors for business continuity (business sustainability). Consumer behavior in choosing a product is primarily determined by several things such as available product design, consumer knowledge, government control over consumers and producers. The role of the Government, Consumers and Producers together forms consumers' character in selecting the products to be consumed; therefore, the part of these three elements becomes essential to study. This study focuses on the role of government control, considering that other variables, namely consumers and producers, have been widely discussed in previous research studies. This study involved 210 respondents who live in Jakarta and surrounding areas. The selection of respondents was carried out by purposive sampling method with the criteria of respondents being groups of people who buy products for their own needs (not for resale). Data analysis was performed using Structure Equation Modeling - Partial Least Square (SEM-PLS). The results revealed that Government Control and Product Design had a direct and significant impact on consumer behavior, while consumer knowledge indirectly affected consumer behavior.